2012
DOI: 10.1186/2191-0855-2-12
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant bromelain production in Escherichia coli: process optimization in shake flask culture by response surface methodology

Abstract: Bromelain, a cysteine protease with various therapeutic and industrial applications, was expressed in Escherichia coli, BL21-AI clone, under different cultivation conditions (post-induction temperature, L-arabinose concentration and post-induction period). The optimized conditions by response surface methodology using face centered central composite design were 0.2% (w/v) L-arabinose, 8 hr and 25°C. The analysis of variance coupled with larger value of R2 (0.989) showed that the quadratic model used for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…The cloning and expression system employed requires the addition of IPTG to trigger the transcription of foreign gene in the plasmid and initiate the translation of recombinant protein. This leads to various changes in the metabolism of host cells [16]. The production of soluble rhGH at different induction time varies widely from 3 to 18 h. The maximum yield of the soluble protein was obtained when the induction time was 10 h (see Fig.…”
Section: Induction Period and Iptg Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloning and expression system employed requires the addition of IPTG to trigger the transcription of foreign gene in the plasmid and initiate the translation of recombinant protein. This leads to various changes in the metabolism of host cells [16]. The production of soluble rhGH at different induction time varies widely from 3 to 18 h. The maximum yield of the soluble protein was obtained when the induction time was 10 h (see Fig.…”
Section: Induction Period and Iptg Concentrationmentioning
confidence: 99%
“…It has also been observed that temperature reduction leads to the low activity of heat shock proteases which are induced during over-expression [5,9,15]. In addition to temperature shifts, the heat-shock response has also been induced by a variety of stress conditions, for example harmful substances such as ethanol [16]. Chemical chaperones are low molecular weight compounds including glycerol and ethanol which have been used to prevent the formation of aggregates into inclusion bodies during invitro folding.…”
Section: Introductionmentioning
confidence: 97%
“…The E. coli expression system is the most widely used host for recombinant protein production (4). Culture conditions, such as induction time, inducer concentration, temperature, and post-induction time, play important roles in recombinant protein expression (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant bromelain expression was conducted as described in our earlier studies [12][13][14]. E. coli BL21-AI cells harboring recombinant bromelain gene were grown in shake flasks overnight in LB media containing 100 μg/ml ampicillin.…”
Section: Enzyme Expressionmentioning
confidence: 99%
“…In that regard, we have reported the cloning and expression of recombinant stem bromelain (recBM) [12], recovery from soluble and insoluble enzyme forms [13], lab-scale optimization of some of its culture cultivation conditions [14] and the enzyme thermal and storage stability [15]. The purpose of the current research is to further characterize the enzyme by focusing on the kinetic studies of recBM using four synthetic substrates;…”
Section: Introductionmentioning
confidence: 99%